2009
DOI: 10.1088/0004-637x/693/2/1736
|View full text |Cite
|
Sign up to set email alerts
|

The James Clerk Maxwell Telescope Nearby Galaxies Legacy Survey. I. Star-Forming Molecular Gas in Virgo Cluster Spiral Galaxies

Abstract: We present large-area maps of the CO J=3-2 emission obtained at the James Clerk Maxwell Telescope for four spiral galaxies in the Virgo Cluster. We combine these data with published CO J=1-0, 24 µm, and Hα images to measure the CO line ratios, molecular gas masses, and instantaneous gas depletion times. For three galaxies in our sample (NGC 4254, NGC4321, and NGC 4569), we obtain molecular gas masses of 7 × 10 8 − 3 × 10 9 M ⊙ and disk-averaged instantaneous gas depletion times of 1.1-1.7 Gyr. We argue that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
90
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 72 publications
(115 reference statements)
12
90
0
Order By: Relevance
“…CO(3-2) single dish observations complemented lower transitions' observations and yielded a wealth of information on the excitation of the molecular gas in galaxy centers (see e.g. Papadopoulos & Seaquist 1999;Papadopoulos & Allen 2000;Dumke et al 2001;Curran et al 2001;Hafok & Stutzki 2003;Yao et al 2003;Weiß et al 2005;Bayet et al 2006;Muraoka et al 2007;Kohno et al 2008;Papadopoulos et al 2008;Wilson et al 2009;Israel 2009) including that of our own Galaxy (Oka et al 2007). These observations showed that the CO(3-2)/(1-0) line ratio generally increases toward the center, where it can reach values greater than unity (in temperature units) in starburst and AGN hosts as well as in the Milky Way (vs. a typical value of 0.4 in galaxy disks).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…CO(3-2) single dish observations complemented lower transitions' observations and yielded a wealth of information on the excitation of the molecular gas in galaxy centers (see e.g. Papadopoulos & Seaquist 1999;Papadopoulos & Allen 2000;Dumke et al 2001;Curran et al 2001;Hafok & Stutzki 2003;Yao et al 2003;Weiß et al 2005;Bayet et al 2006;Muraoka et al 2007;Kohno et al 2008;Papadopoulos et al 2008;Wilson et al 2009;Israel 2009) including that of our own Galaxy (Oka et al 2007). These observations showed that the CO(3-2)/(1-0) line ratio generally increases toward the center, where it can reach values greater than unity (in temperature units) in starburst and AGN hosts as well as in the Milky Way (vs. a typical value of 0.4 in galaxy disks).…”
Section: Introductionmentioning
confidence: 84%
“…We estimated the flux missed by the SMA due to the short spacings inherently missing in interferometric observations by comparing to the single dish data published by Wilson et al (2009) for NGC 4569 and by Israel (2009) for NGC 4826. We compared the total flux within an aperture of ∼36 in diameter after correcting the SMA data for the primary beam attenuation and degrading to the resolution of the single dish data (14.5 ).…”
Section: Observations and Data Processingmentioning
confidence: 99%
“…For those GMAs with HII regions, SFR ranges between 2.1 × 10 −5 -0.3 M ⊙ yr −1 , with a median value 1.8 × 10 −3 M ⊙ yr −1 . The total SFR in the 165 GMAs is ∼ 2 M ⊙ yr −1 , accounting for ∼ 75% of the global SFR derived from the Hα + 24 µm data (Wilson et al 2009). …”
Section: Hii Regions and Sfr Of Gmasmentioning
confidence: 97%
“…Bigiel et al (2008) found that if one only considers the surface-density of molecular gas the value of N is 1. Wilson et al (2009) used CO 3-2 observations to map the ISM in the same galaxies we have considered in this paper and found little variation in the gas depletion timescale across the disks, which implies N 1. Our values of N are higher than this, whichever method we use for mapping the ISM.…”
Section: The Star-formation Rates In M 99 and M 100mentioning
confidence: 94%
“…We have used the maps of the star-formation rate in these galaxies produced by Wilson et al (2009), who combined 24-μm Spitzer images and Hα images to correct for the effect of dust obscuration, following the prescription of Calzetti et al (2007). We have produced maps of the gas in each galaxy by combining the CO 1-0 maps of Kuno et al (2007) and the HI maps from the VIVA survey (Chung et al 2009).…”
Section: The Datamentioning
confidence: 99%